Tragic–Comic Elements in Fredrik Backman’s Novel a Man Called Ove: A Linguistic Pragmatic and Stylistic Perspective - Krajnc Ivič, Mira (ZORA 160: Imenitnost slovenščine sto let po Pleteršniku, 2026)
The article offers a pragmatic and stylistic analysis of Fredrik Backman’s A Man Called Ove. It shows that the interplay of tragic and humorous elements emerges from deliberate flouting of the Cooperative Principle and residual pragmatic excess. These mechanisms play a crucial role in character construction and in guiding the reader’s empathy. All the above will be examined also through questionnaire data.